2016
DOI: 10.1016/j.susc.2015.10.061
|View full text |Cite
|
Sign up to set email alerts
|

Enantiomeric separations of chiral pharmaceuticals using chirally modified tetrahexahedral Au nanoparticles

Abstract: Tetrahexahedral (THH, 24-sided) Au nanoparticles modified with D-or L-cysteine (Cys) have been used as enantioselective separators of the chiral pharmaceutical propranolol (PLL) in solution phase. Polarimetry has been used to measure the rotation of linearly polarized light by solutions containing mixtures of PLL and Cys/THH-Au NPs with varying enantiomeric excesses of each. Polarimetry yields clear evidence of enantiospecific adsorption of PLL onto the Cys/THH-Au NPs. This extends prior work using propylene o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 19 publications
0
21
0
Order By: Relevance
“…In principle, the addition of a racemic probe to the solution should induce no change in optical rotation, unless that probe interacts enantiospecifically with the chiral Au-NPs such that one enantiomer adsorbs preferentially on the Au-NP surface. Detection of this separation by optical polarimetry also requires that the specific optical rotation constant of the adsorbed probe enantiomer differs from its value in solution [ 12 , 13 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In principle, the addition of a racemic probe to the solution should induce no change in optical rotation, unless that probe interacts enantiospecifically with the chiral Au-NPs such that one enantiomer adsorbs preferentially on the Au-NP surface. Detection of this separation by optical polarimetry also requires that the specific optical rotation constant of the adsorbed probe enantiomer differs from its value in solution [ 12 , 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…In previous work, we have shown that L- and D-cysteine (Cys, HO 2 CCH(NH 2 )CH 2 SH) modified surfaces of Au-NPs are capable of enantiospecific adsorption of racemic propylene oxide (PO) [ 11 , 12 ] and the chiral pharmaceutical propranolol hydrochloride [ 13 ]. In these studies, Au-NPs were either spherical or tetrahexahedral (24-sided) in shape.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the potential of metal NPs in separation science has been already well recognized due to their easy synthesis procedure, large s / v ratio, controllable particle size, narrow size distribution, extraordinary biocompatibility, molecular detection properties, etc. [24,89,125].…”
Section: Enantiomeric Separation By Chiral Nanoparticlesmentioning
confidence: 99%